Corruption And Development In Nigeria: A Psychological Perspective (Global Journal of Human-Social Science, 2012)
Corruption is an 'evil': a social vice that hampers national development. It is a global phenomenon that devastatingly affects developing economies. It is an act, internalized acts and, or, behavior by observing some significant persons around us who are otherwise referred to as our 'model'. Since corruption is a learned behaviour, this paper, thus, attempts to analyze it from a psychological perspective, using the relevant psychological theories for analysis. It is recommended that if we appreciate the relevance of Psychologists as professional human helpers and society builders, they would be handy in helping to reshape our orientations regarding value appreciation most especially in Nigeria, through their use of behavioural change interventions. Since corruption is a learned behavior, it can be unlearnt through some forms of situational and environmental manipulations. A model is presented to explain how behavior is influenced by both a person and his environment.
Keywords: Corruption; Development; Manipulations; Nigeria; Psychology